Studium vertikální mobility těžkých kovů a jejich transferu do hub - Jurnečka, Roman (Vysoké učení technické v Brně. Fakulta chemická, 2021)
Tato bakalářská práce se věnuje problematice kontaminace lesních půd a jedlých hub olovem, kadmiem, mědí a zinkem v oblasti Jeseníků, konkrétně v polesích Domašov a Vápenná. Odběr vzorků proběhl na 12 lokalitách s rozdělením na smrkové a bukové porosty. Pro stanovení obsahu vybraných těžkých kovů byla zvolena atomová absorpční spektrometrie AAS ContrAA 800D. Na základě změřených hodnot koncentrací studovaných kovů a dalších půdních vlastností byly vytvořeny závislosti pro stanovení vertikální mobility vybraných kovů v půdním profilu. Vertikální mobilita je závislá na fyzikálně-chemických vlastnostech půdy (pH, obsah C a S). Byla zjištěna závislost obsahu vybraných těžkých kovů v půdě na hodnotě pH půdy. V případě olova byla potvrzena sorpční schopnost půdní organické složky. Na hřibu žlutomasém byl zjištěn rizikový a nadlimitní obsah Pb, Cd a Cu. Největší biologickou dostupnost vykazuje kadmium. Olovo bylo vyhodnoceno jako prvek s nejnižší mobilitou.

This bachelor thesis deals with the issue of contamination of forest soils and edible mushrooms with lead, cadmium, copper and zinc in the Jeseníky Mountains, specifically in the Domašov and Vápenná forests. Sampling took place at 12 localities, divided into spruce and beech stands. Atomic absorption spectrometry AAS ContrAA 800D was chosen to determine the content of selected heavy metals. Based on the measured values of the concentrations of the studied metals and other soil properties, dependences were created to determine the vertical mobility of selected metals in the soil profile. Vertical mobility depends on the physico-chemical properties of the soil (pH, C and S content). The dependence of the content of selected heavy metals in the soil on the pH value of the soil was found. In the case of lead, the sorption capacity of the soil organic component was confirmed. The risk and above-limit content of Pb, Cd and Cu was found on the yellow-boletus mushroom. Cadmium shows the highest bioavailability. Lead was evaluated as the element with the lowest mobility.
The study of vertical mobility of heavy metals and their transfer to mushrooms
Keywords: Olovo; kadmium; měď; zinek; AAS; vertikální mobilita; bioakumulace; jedlé houby; lesní půdy; Lead; cadmium; copper; zinc; AAS; vertical mobility; bioaccumulation; edible mushrooms; forest soils